EFFECT OF “SENAM PERMATA-KU” COMPARED WITH WARM COMPRESS ON THE AMPLITUDE OF ACCOMMODATION IN COMPUTER VISION SYNDROME PATIENTS - Setiawan, Teguh; Nugroho, Trilaksana; Dharma, Andhika Guna; Rahmi, Fifin L.; Sadasih, Wisnu (Majalah Oftalmologi Indonesia, 2023)
Introduction and Objective: The COVID-19 pandemic has virtually made many work activities, resulting in increased use of Visual Display Terminals (VDT) at work and home. Excessive close-range activities due to the use of VDT causes Computer Vision Syndrome (CVS). Various therapies, such as ocular yoga and warm compress, have been created to reduce CVS-related complaints. Diponegoro University developed “Senam PERMATA-KU” as an alternative therapy to reduce complaints related to CVS. This study compares the effect of “Senam PERMATA-KU” and periocular warm compress on the amplitude of accommodation (AA) value in patients with CVS. Methods: The study subjects were divided into “Senam PERMATA-KU” group (22 people) and periocular warm compress group (20 people) with each treatment for two weeks. CVS score was measured using CVS-Questionnaire and AA using Prince’s rule. Both variables were assessed before and after treatment. Data were collected and analyzed using a statistical computer program. Result: “Senam PERMATA-KU” group experienced a significant increase in monocular and binocular AA (p<0.001 and p=0.006), while periocular warm compress did not show a significant difference (p=0.982 and p=0.483). The mean delta of monocular and binocular AA between groups differed significantly (p=0.001 and p=0.034). The mean CVS scores in both groups have significant improvement (p<0.001), while the mean delta CVS scores between groups was not significant (p=0.522). Conclusion: “Senam PERMATA-KU” for two weeks significantly increased monocular and binocular AA, while periocular warm compress showed no significant difference. “Senam PERMATA-KU” and periocular warm compress can significantly reduce CVS score, whereas the difference between the two is insignificant.